2009
DOI: 10.1088/1742-6596/180/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

2D and 3D core-collapse supernovae simulation results obtained with the CHIMERA code

Abstract: Much progress in realistic modeling of core-collapse supernovae has occurred recently through the availability of multi-teraflop machines and the increasing sophistication of supernova codes. These improvements are enabling simulations with enough realism that the explosion mechanism, long a mystery, may soon be delineated. We briefly describe the CHIMERA code, a supernova code we have developed to simulate core-collapse supernovae in 1, 2, and 3 spatial dimensions. We then describe the results of an ongoing s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 17 publications
4
110
0
Order By: Relevance
“…CHIMERA 9 is a multi-physics code built specifically for multidimensional simulation of CCSNe that has been under development for more than a decade (Hix et al 2001;Bruenn 2005;Bruenn et al 2006;Messer et al 2007Messer et al , 2008Bruenn et al 2009aBruenn et al , 2009bBruenn et al , 2013. It is a combination of separate codes for hydrodynamics, gravity,neutrino transport, neutrino opacities,nuclear EoSs, coupled by a layer that oversees data management, parallelism, I/O, and control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CHIMERA 9 is a multi-physics code built specifically for multidimensional simulation of CCSNe that has been under development for more than a decade (Hix et al 2001;Bruenn 2005;Bruenn et al 2006;Messer et al 2007Messer et al , 2008Bruenn et al 2009aBruenn et al , 2009bBruenn et al , 2013. It is a combination of separate codes for hydrodynamics, gravity,neutrino transport, neutrino opacities,nuclear EoSs, coupled by a layer that oversees data management, parallelism, I/O, and control.…”
Section: Methodsmentioning
confidence: 99%
“…Though two decades have passed, 2D models are only now beginning to fill in the CCSN landscape in a fashion done previously in 1D. Twodimensional simulations including spectral neutrino transport, general relativistic corrections to 2D Newtonian self gravity or approximate 2D general relativistic self gravity, all relevant neutrino weak interactions, including neutrino-energy-coupled scattering and electron capture on nuclei modeled to include nucleon-nucleon interactions, and sophisticated nuclear equations of statehave been performed with two codes thus far, VERTEX (Buras et al 2006a(Buras et al , 2006bMarek & Janka 2009;Müller et al 2012aMüller et al , 2012b and CHIMERA (Bruenn et al 2006;Messer et al 2007;Bruenn et al 2009aBruenn et al , 2013, though these codes use the "ray-by-ray" (RbR) approximation to neutrino transport rather than a fully 2D transport implementation. (We will discuss the RbR approximation in Sections 2 and 5.3.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three independent groups worldwide (Bruenn et al 2009, Marek & Janka 2009, and Suwa et al 2010) have now reported neutrinodriven explosions, beginning with a range of stellar progenitor masses from 11 to 25 M . In all cases, the standing accretion shock instability (SASI; Blondin, Mezzacappa, & DeMarino 2003) couples with neutrino heating to power the explosions and thus plays a central role.…”
Section: Supernovae (M Limongi a Tornambè A Mezzacappa)mentioning
confidence: 99%
“…Neutrinos generated in the core nuclear reaction of heavy ions may drive supernova explosion. The neutrino mechanism is much more viable when the effects of three-dimensional hydrodynamics, particularly convection, are included (Fryer & Warren 2002, 2004Hammer et al 2010;Bruenn et al 2009;Blondin & Shaw 2007). Its success crucially depends on the rate of neutrino production in the core and the rate of neutrino absorption at the mantle.…”
Section: Introductionmentioning
confidence: 99%